(untitled) (Bangladesh Armed Forces Medical Journal, 2024)
Background: Oral and maxillofacial diseases encompass a wide range of conditions in and around oral cavity and in maxillofacial region. It includes maxillofacial trauma, cyst and tumour of jaw bones, conditions involving impacted wisdom teeth, oral premalignant and malignant lesions, fascial space infection around maxillofacial region, temporomandibular joint disorder, dental implantology, salivary gland disorder and congenital defects of jaw bones. Maxillofacial region is more vulnerable to sustain injuries in the battlefield. In peace time, various maxillofacial diseases reduce the overall performances of the troops. The aim of this study is to delineate rank wise distribution of armed forces personnel reported with maxillofacial diseases, gender distribution, types of maxillofacial diseases, different types of surgical procedures performed and types of anesthesia used. Methods: A descriptive cross-sectional study was conducted to assess the prevalence of maxillofacial diseases among the armed forces personnel and their entitled family members during the period of 1st January 2019 to 31st December 2019 in Military Dental Centre, Cumilla. Purposive sampling technique and semi structured questionnaire was used to include the patients in this study.Data were analyzed by using Statistical Packages for Social Sciences (SPSS) version 25. Results: A total of 170 cases were evaluated and treated. Male patients were 110(65%) and female were 60(35%). Among the military personnel numbers of sainik (privates) were highest 32(35%). Impacted wisdom teeth cases were mostly found 80(47%). In case of impacted teeth mesio angular impactions were most 35(35%). In case of maxillofacial pathological conditions cystic lesions were most in number 22(39%) (n=56). Maxillofacial soft tissue laceration cases were highest 05(29%) (n=17) among all trauma patients. Surgical extraction of wisdom teeth were mostly performed surgery 80(59%) (n=138). In regards to administration of anesthesia, 128(93%) cases were performed under local anesthesia and 10(7%) were under general anesthesia. Conclusion: The present study imparts valuable perception about the types and prevalence of maxillofacial diseases and the treatment modalities among the armed forces personnel and their families in Cumilla area. Bangladesh Armed Forces Med J Vol 56 No (2) December 2023, pp 24-30